Crossroads of PI3K and Rac pathways - Campa, Carlo C (Small GTPases, 2015)
Rac and PI3Ks are intracellular signal transducers able to regulate multiple signaling pathways fundamental for cell behavior. PI3Ks are lipid kinases that produce phosphorylated lipids which, in turn, transduce extracellular cues within the cell, while Rac is a small G protein that impacts on actin organization. Compelling evidence indicates that in multiple circumstances the 2 signaling pathways appear intermingled. For instance, phosphorylated lipids produced by PI3Ks recruit and activate GEF and GAP proteins, key modulators of Rac function. Conversely, PI3Ks interact with activated Rac, leading to Rac signaling amplification. This review summarizes the molecular mechanisms underlying the cross-talk between Rac and PI3K signaling in 2 different processes, cell migration and ROS production.